Cash Flow Management Assistance for Micro, Small, and Medium Enterprises (MSMEs) in Bojonegoro and Tuban - Monica Resavita; Nanang Setiawan (Jurnal Pengabdian Masyarakat Al-Fatimah, 2024)
MSMEs are the backbone of Indonesia's economy. One of the challenges currently faced by MSMEs is operational difficulties, including limited financial and administrative capacity. This limitation makes it difficult for MSMEs to prepare working capital and meet short-term obligations. The objective of this research is to analyze financial management in five MSMEs in the Tuban and Bojonegoro regencies and provide assistance in cash flow management. This assistance is expected to improve financial and administrative capacity, thereby benefiting their business development. Assistance was provided to five MSMEs, namely Toko Kelontong Nurul Muttaqin and Hijab by Azkia Scraft from Bojonegoro, Hendry Aldy MUA, Mebel UD Jaya Makmur, and Toko Kelontong Subur Makmur from Tuban. The research results refer to four indicators of financial management and show that all MSMEs studied use budgeting plans, keep simple records, and exercise adequate control. However, not all MSMEs understand the reporting indicators in their financial statements. The analysis results from this research will serve as material for the assistance provided over approximately three months